2018
DOI: 10.1103/physrevd.97.054505
|View full text |Cite
|
Sign up to set email alerts
|

Searching for beauty-fully bound tetraquarks using lattice nonrelativistic QCD

Abstract: Motivated by multiple phenomenological considerations, we perform the first search for the existence of abbbb tetraquark bound state with a mass below the lowest noninteracting bottomonium-pair threshold using the first-principles lattice nonrelativistic QCD methodology. We use a full S-wave color/spin basis for thebbbb operators in the three 0 þþ , 1 þ− and 2 þþ channels. We employ four gluon field ensembles at multiple lattice spacing values ranging from a ¼ 0.06-0.12 fm, all of which include u, d, s and c q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(97 citation statements)
references
References 71 publications
1
89
0
Order By: Relevance
“…This observation is consistent with those in Refs. [74,79,82]. The lowest bbbb mass in [79] and ours are similar.…”
Section: B the Bbbb And Cccc Systemssupporting
confidence: 76%
See 1 more Smart Citation
“…This observation is consistent with those in Refs. [74,79,82]. The lowest bbbb mass in [79] and ours are similar.…”
Section: B the Bbbb And Cccc Systemssupporting
confidence: 76%
“…If the P-wave cccc state exists where the orbital angular momentum contributes some repulsion, the lower ground tetraquark states should also exist. Recently, there are further discussions about the properties of fully-heavy tetraquarks [74][75][76][77][78][79][80][81][82][83][84].…”
mentioning
confidence: 99%
“…[22], and the product of its production cross-section at the LHC and the branching fraction to four muons is estimated to be of O(1 fb). However, recent lattice QCD calculations do not find evidence for such a state in the hadron spectrum [23].…”
Section: Introductionmentioning
confidence: 96%
“…[46] investigated the mass spectra of the QQQQ states in the Chromomagnetic interaction (CMI) model and concluded that no stable QQQQ states exist. Later, several other approaches, such as the nonrelativistic chiral quark model [47,48], the lattice QCD [49] and other models [50,51] also do not support the existence of the bound QQQQ states.…”
Section: Introductionmentioning
confidence: 99%